Composição corporal de minerais em ovelhas gestantes da raça Santa Inês - Luciana Freitas Guedes (2012)
The objective was to evaluate the body composition of macro and micro sheep of Santa Inês pregnant and non pregnant women subjected to two nutritional managements. 73 females were used at different stages of gestation and ten non-pregnant ewes as reference animals totaling 83 animals in the experimental testing distributed in a completely randomized 2 x 4 and two nutrient managements (restricted and unrestricted) and four stages of pregnancy (0, 90, 110, 130 and 140 days). The sheep were slaughtered according to the gestational period following the protocol submitted to the Ethics Committee on Animal Experiments (protocol # 77/2006). The mineral solution was obtained by wet. Phosphorus was determined by colorimetry, sodium and potassium determined in flame spectrophotometer. Analyses of calcium, magnesium, manganese, zinc, copper and iron were performed by atomic absorption spectrophotometry. The mineral content (macro and micro) were determined by the concentration of the carcass, brain + feet, visceral fat, viscera, organs, skin, blood, mammary gland, uterus (uterus + placenta), fetus and fetal fluid. The gestational period affected the weight of body components of sheep except for fetal fluid. The level of 15% energy protein restriction imposed did not affect the concentration of any of the minerals studied here. The estimation of body composition to pregnant sheep was found from 17.15 to 25.79 g Ca, 11.03 to 17.62 g of P, 2.14 to 2.86 g Na, 1.89 to 2, 65 g of potassium, 0.31 to 0.50 g of Mg from 4860.50 to 7903.40 mg of Fe, from 2359.16 to 3077.50 mg Zn; 267.06 to 699.22 mg Cu and 142.21 to 300.59 mg of Mn per kg EBW depending on the gestational stade. It is possible to use regression equations to predict the amount of mineral retained in the fetus due to its weight, whatever the nutritional management adopted.